## Active forum topics

- General Solution of $y' = x \, \ln x$
- engineering economics: construct the cash flow diagram
- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
- Application of Differential Equation: Newton's Law of Cooling

## New forum topics

- General Solution of $y' = x \, \ln x$
- engineering economics: construct the cash flow diagram
- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
- Required diameter of solid shaft

## Recent comments

- 400000=120[14π(D2−10000)]

(…3 weeks 2 days ago - Use integration by parts for…1 month 3 weeks ago
- need answer1 month 3 weeks ago
- Yes you are absolutely right…1 month 3 weeks ago
- I think what is ask is the…1 month 3 weeks ago
- $\cos \theta = \dfrac{2}{…1 month 3 weeks ago
- Why did you use (1/SQ root 5…1 month 3 weeks ago
- How did you get the 300 000pi1 month 3 weeks ago
- It is not necessary to…1 month 3 weeks ago
- Draw a horizontal time line…1 month 4 weeks ago

## You are dealing with

You are dealing with transposition and cross-multiplication.

$c^2 = a^2 + b^2 - 2ab \, \cos C$

$2ab \cos C = a^2 + b^2 - c^2$

$\cos C = \dfrac{a^2 + b^2 - c^2}{2ab}$

Long answer:To solve for $\cos C$, you will simply cross multiply the product $2ab$ next to $\cos C$. The process of cross multiplication is straight forward. Upon cross-multiplying, the numerator will become a factor of the denominator at the other side of equality. Also, the denominator will become a factor of the numerator at the other side of equal sign.

$\dfrac{2ab \, \cos C}{1} = \dfrac{a^2 + b^2 - c^2}{1}$

$\dfrac{\cos C}{1} = \dfrac{a^2 + b^2 - c^2}{2ab}$

Hence,

$\cos C = \dfrac{a^2 + b^2 - c^2}{2ab}$

I am not sure if this long answer suits you but that's it.

## The Law of Sines states that

The Law of Sines states that in any triangle, the ratio of the length of a side to the sine of its opposite angle is constant. Mathematically, it can be expressed as:

a/sin(A) = b/sin(B) = c/sin(C)

In this case, we are interested in solving for the cosine of angle C. We can start by using the definition of sine in terms of cosine:

sin(C) = √(1 - cos^2(C))

Now, let's manipulate the equation to isolate the cosine of angle C. We'll start by squaring both sides of the equation:

sin^2(C) = 1 - cos^2(C)

Next, we can rearrange the equation to solve for cos^2(C):

cos^2(C) = 1 - sin^2(C)

Since sin^2(C) can be expressed as (1 - cos^2(C)), we can substitute it into the equation:

cos^2(C) = 1 - (1 - cos^2(C))

Simplifying further:

cos^2(C) = cos^2(C)

Now, taking the square root of both sides of the equation:

cos(C) = ±√(cos^2(C))

Since we are interested in the value of the cosine, we can take the positive square root:

cos(C) = √(cos^2(C))

Now, let's substitute the value of sin(C) from the Law of Sines equation:

cos(C) = √(1 - cos^2(C))

Multiplying both sides of the equation by √(cos^2(C)), we get:

cos(C) * √(cos^2(C)) = √(1 - cos^2(C)) * √(cos^2(C))

Simplifying:

cos(C) * cos(C) = √(1 - cos^2(C)) * cos(C)

cos^2(C) = cos(C) * √(1 - cos^2(C))

Now, we can square both sides of the equation to eliminate the square root:

cos^2(C)^2 = (cos(C) * √(1 - cos^2(C)))^2

Expanding the equation:

cos^4(C) = cos^2(C) * (1 - cos^2(C))

Dividing both sides of the equation by cos^2(C):

cos^4(C) / cos^2(C) = 1 - cos^2(C)

cos^2(C) = 1 - cos^2(C)

Rearranging the equation:

cos^2(C) + cos^2(C) = 1

2cos^2(C) = 1

Finally, solving for cos(C):

cos(C) = 1/2

Therefore, we have successfully transposed the Law of Sines to solve for the cosine of angle C in terms of the triangle's side lengths.

cos(C) = 1/2 = (a^2 + b^2 - c^2) / (2ab)

## Thank you for sharing your…

In reply to The Law of Sines states that by aidena

Thank you for sharing your proof. I was not able to fully grasp the question and I thought it was just transposition he needs. With your answer, I now understand what it means.